PENGARUH KECERDASAN EMOSIONAL TERHADAP KEMAMPUAN MENGELOLA KONFLIK DI LEMBAGA PEMASYARAKATAN KLAS IIA WANITA TANGERANG\ - Mirrah Apsari Nubi (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2017)
Abstract This study aims to determine the effect of emotional intelligence with the ability to manage a conflict. The experiment was held in Tangerang. The method used is ex post facto method with quantitative approach. Population sample of inmates or residents guided the study sample as many as 362 and as many as 70 people with a random sampling technique. The instrument used is to test the ability to manage conflict as the dependent variable and the scale on emotional intelligence as independent variables. From anareg equation Y = 1,86 + 0,16X, Fcount = 47.19, Ftable = 3.99, because the regression is Fcount> of Ftable is very significant. To determine the linearity seen as Fcount = 1.14, and Ftable = 1.76, so it means the form of linear regression Fcount <Ftable. For Ttest, the path coefficient of 0.640 with a determinant coefficient of r ² = 0.409. It’s means that emotional intellingence gave 40.9% of the ability to manage conflict. Tcount got (6.88)> Ttable (1.67) at α 0.05. So the hypothesis is “There is the any influence of emotional intelligence with ability of Managing Conflict